Análise da dinâmica do glicoproteoma de trichoderma asperelloides durante o micoparasitismo - Naoum, Stéphanie (2022)
Glycosylation is a post-translational modification that occurs in most cells and is an important mechanism for several cellular processes such as protein secretion, cell signaling, protein translocation and stability, maintenance of cell structure and receptor-ligand interactions. In fungi there is a set of enzymes specialized in glycosylation of proteins, exerting functions related to the structure of the cell wall and the cell as a whole, assisting in integrity, growth, differentiation and signaling. Fungi of the genus Trichoderma are known for their ability to biocontrol through mycoparasitism mechanisms involving the production of cell wall degrading hydrolytic enzymes. Therefore, the objective of this work was to identify the N-glycosylated proteins produced by T. asperelloides (TR356) during mycoparasitism. The Concanavalin A (ConA) affinity chromatography technique was used to enrich the samples and select N-glycated glycoproteins with oligomannosidic structure. In the interaction between the fungi, the contact condition showed a difference in the protein content when compared to the control samples. The specific activities of the enzymes β-1,3-exoglycanase, β-1,3-endoglycanase, chitinase, N-acetyl-glucosaminidase, β-glucosidase, acid phosphatase, α-mannosidase, α-arabinofuranosidase and demonstrated a significant increase in activities in conditions before contact and contact. Several proteins were identified in the samples using the mass spectrometry technique. A total of 253 proteins were identified in the control sample. In samples referring to before contact and contact between T. asperelloides (TR 356) and S. sclerotiorum the number of identified proteins was higher, 582 and 524 proteins, respectively. We can infer that the presence of the pathogen S. sclerotiorum in the same environment as T. asperelloides stimulates the production of specific proteins for this situation, necessary for mycoparasitism. Glycoproteins with different amounts of N-glycosylation sites involved in mycoparasitism were identified, and the number of glycoproteins and N-glycosylation sites increased in pre-contact and in-contact situations. Most secreted proteins are involved in carbohydrate metabolism and transport, cell signaling, and post-translational modifications and folding. The identified proteins of the intracellular environment are involved in post-translational modification and protein folding, in carbohydrate metabolism and transport, and in cellular metabolism in general. Finally, we observed that a significant number of identified proteins still do not have a defined function, which can be considered an important source of new studies and new knowledge in relation to mycoparasitism.